CaO-based meshed hollow spheres for CO2 capture. (2nd October 2015) - Wang, Shengping; Shen, Hui; Fan, Shasha; Zhao, Yujun; Ma, Xinbin; Gong, Jinlong
Abstract: This paper describes the synthesis of CaO-based meshed hollow spheres using colloidal carbon as a template via a urea hydrolysis method for CO2 absorption. The features of meshed hollow spheres and the CO2 absorption performance of the absorbent in calcinations/carbonation cycles were investigated employing scanning electron microscope (SEM), X-ray diffraction (XRD), transmission electron microscope (TEM), and thermo gravimetric analyzer (TGA). The absorbent had an excellent performance with a higher capacity and a better stability compared to the reference absorbents, which were prepared without using the carbon sphere templates or the urea hydrolysis. The initial capacity of the absorbent was about 75% that maintained 63% after the 28th cycle absorption/desorption process. It was suggested that the meshed hollow sphere structure was favorable for absorption capacity and stability of the absorbent due to the formation of uniform, disperse, and loose CaO particles. Graphical abstract: Highlights: CaO-based meshed hollow spheres were synthesized using colloidal carbon as a template via a urea hydrolysis method. The CaO absorbent had a high capacity and a good stability. The high performance of CaO absorbent is due to the formation of uniform, disperse, and loose CaO particles.